Пам’яті С. К. Кульжинського - Супруненко, О.Б. (Археологія, 2018)
Наводиться короткий біографічний нарис відомого музейника, етнографа, географа, природознавця і педагога, огляд його археологічної діяльності та заходів із відзначення 150-річного ювілею С.К. Кульжинського у м. Лубни на Полтавщині у травні 2017 р. It is 150th anniversary of Sergii Klymentiiovych Kulzhynskyi (1867—1943), one of the first explorers of pysanka-making in Ukraine, museums employee, ethnographer, geographer and pedagogue. His life and work was connected to the history of Lubny for more than half of a century. Life and scientific path of Lubny scholar and museum employee was not observed in numerous publications and some great gaps in his biography can be noticed. The article aims to fill these gaps in some way. Many biographical facts about life of the explorer of the Sula River area antiquities are found, his biographical sketch with synopsis of his archaeologic and publishing activity is composed. S.K. Kulzhynskyi’s role in forming the K.M. Skarzhynska Lubny Museum gathering, passing its collection as a gift to the Natural Historic Museum of Poltava Governorate Zemstvo is specially outlined. Presented are the new data concerning the late-Lubny life period of the scholar as a Head of the Lubny Ukrainian Folk Museum, a reader and docent of the Lubny social Training Institute (later Pedagogic and Teacher-training Institute), and the time of occupation of the town by the fascists. Places of death and burial of S.K. Kulzhynskyi are found. Photos and description of gravestone on scholar’s grave at old Lubny town cemetery down D. Siryk Street, placed before the anniversary, are presented. The paper is supplied with a brief report on a scientific conference in Lubny of Poltava Oblast in May, 2017. Исполнилось 150 лет со дня рождения одного из первых исследователей писанкарства Украины, сотрудника музеев, этнографа, археолога, географа и педагога Сергея Kлиментиевича Kульжинского (1867—1943). Жизнь и деятельность ученого на более чем полстолетия во времени связаны с историей города Лубны. Жизненному и творческому научному пути ученого и музейного сотрудника посвящено совсем немного публикаций, в которых заметны лакуны в биографии исследователя. Статья ставит цель определенным образом восполнить эти пробелы. К юбилею восполнено много новых фактов в биографии исследователя древностей Посулья, составлен его биографический очерк с обзором собирательской, археологической и издательской деятельности. Особо подчеркнута роль С.К. Кульжинского в формировании собрания Лубенского музея Е.Н. Скаржинской, передаче коллекций этого музея в дар Естественно-историческому музею Полтавского губернского земства. Приводятся новые данные по позднему лубенскому периоду жизни ученого как руководителя Лубенского Украинского Народного музея, преподавателя и доцента Лубенского Института социального воспитания (позже педагогического, затем учительского института), а также времени фашистской оккупации города. Установлены места смерти и погребения С.К. Кульжинского. Представлены фото и описание плиты-надгробия на могиле ученого на старом Лубенском городском кладбище по ул. Д. Сирыка, установленной в предверии юбилея. Исследование дополнено кратким отчетом о научной конференции, проведенной в г. Лубны Полтавской области в мае 2017 г.